Distribution and ranging area of elephant in Simpan Panti Forest, Kota Tinggi, Johor, Malaysia - NURUL HAZIRAH NOR HASSAN; Nazirah Mohamad Abdullah; NOR ATIQAH NORAZLIMI; Salman Saaban; MUHAMMAD FADLLI AB YAZI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hassan NHN, Abdullah NM, Norazlimi NA, Saaban S, Yazi MFA. 2023. Distribution and ranging area of elephant in Simpan Panti Forest, Kota Tinggi, Johor, Malaysia. Biodiversitas 24: 5731-5738. Home range estimation is one of the most used animal ecology studies using a Geographic Information System (GIS). One adult female Asian elephant (Elephas maximus Linnaeus, 1758) was fitted with a telemetry satellite collar African Wildlife Tracking (AWT) to determine its home range size distribution through its ranging behaviour and to identify the relationship between the GPS collar location record and the area covered. The home range estimation was determined using GPS collar location data from a satellite telemetry system and analyzed by using the Minimum Convex Polygon methods. GPS collar location data were obtained from the Department of Wildlife and National Parks (DWNP). The movement of elephant data was overlayed with the land use data of the Simpan Panti Forest (Hutan Simpan Panti), Kota Tinggi District, Johor, Malaysia before being exported to ArcGIS Pro software. The ArcGIS Pro software can estimate this Asian elephant home range sizes by using the MCP method for twelve months, from 1 June 2019 until 31 May 2020. The total home range size is 447.17 km². Home range size is estimated to be 31.77 to 303.86 km² in one year. The size of this home range has presumably been impacted by extensive human activities such as highways and settlement areas. So, good and strong management is needed to control this conflict for humans to live in harmony in one area and protect the remaining forest reserve area from expanding to agricultural activity and human development areas.